Educação popular e questão social : interconexões possíveis a partir do método pedagógico do Instituto de Educação Josué de Castro em Veranópolis/RS - Silva, Daniela Quadros da (My University, 2018)
The topic of this research study is “popular education and social question” and as a case study focuses on the practices of Instituto de Educação Josué de Castro (IEJC), located in the city of Veranópolis/RS. This research approaches the following question: “At what level the pedagogic methodology of popular education from IEJC contributes or not to bring social question and the resistance to those to the surface from both an educators and students point of view?” More specifically, this paper examines reflective and theoretical aspects of social issues, popular education and social movements, especially MST on its instructional dimension. To understand and framework the history of Instituto de Educação Josué de Castro highlighting the theoretical foundation that sustains its pedagogic methodology as well as identify potential topics of popular education materialized on its teachings; to identify the contemporary expressions of social question inherent to the daily existence of IEJC educators and to determine their own personal interpretation of those expressions; investigate which resistance strategies are mobilized by IEJC educators to counterbalance the social question experienced by them. To elect the limits and the opportunities identified by both IEJC students and instructors in regards to the popular education elements as part of its pedagogic methodology and how to raise awareness about social question and the tactics used to conceal their utmost expression. The topic of choice is justified by the current political environment in Brazil, which makes extremely relevant to unveil not only the social question experienced by large portions of the population, such as poverty, unemployment, urban violence, lack of access to its legitimate citizenship rights, among others, but also the resistance strategies to suppress their discussion. The approach is primarily qualitative, utilizing empirical analysis of semi-structured interviews, documental analysis, field research and subsequent organization and interpretation of the data collected with the use of content analytical method. The reflections are examined through the lens of history. The results show the potential of the popular education incorporated by the pedagogic methodology of IEJC to unveil social question in both its inequality and resistance dimensions.
A pesquisa tem como objeto de estudo “educação popular e questão social” e como cenário o Instituto de Educação Josué de Castro (IEJC), localizado no município de Veranópolis/RS. A investigação proposta parte da seguinte problematização: de que maneira os elementos de educação popular contidos no método pedagógico do IEJC podem ou não contribuir para o desvelamento da questão social e para a resistência às suas expressões na concepção de seus educadores e educandos? Mais especificamente, deseja-se verificar aspectos teóricos e reflexivos acerca da questão social, da educação popular e dos movimentos sociais, especialmente do MST em sua dimensão educativa; Conhecer e sistematizar a trajetória do Instituto de Educação Josué de Castro evidenciando os fundamentos teóricos que embasam seu método pedagógico e identificando possíveis pressupostos da educação popular que nele se materializam; Identificar as expressões da questão social que se presentificam no cotidiano de vida dos educandos do IEJC e qual é a compreensão que os mesmos têm em relação a estas expressões; Investigar que possíveis estratégias de resistência são mobilizadas por educandos do IEJC diante das expressões da questão social por eles vivenciadas e, por fim, elencar os limites e possibilidades identificados pelos educadores e educandos do IEJC quanto aos elementos de educação popular contidos no seu método pedagógico, para o desvelamento da questão social e resistência às suas expressões. Justifica-se a escolha deste tema com base no próprio cenário político vivenciado no Brasil que torna relevante e necessária a pesquisa voltada para possíveis alternativas de reconhecimento da realidade e potencialização de estratégias de resistência às múltiplas expressões da questão social que se reconfiguram nop contexto societário e se materializam no cotidiano de vida de inúmeros sujeitos através do desemprego, da pobreza, da violência, do não acesso aos direitos de cidadania, entre outras situações. Em relação à abordagem, a pesquisa é prioritariamente qualitativa, utilizando-se para o desenvolvimento do corpus empírico de entrevistas semiestruturadas, análise documental, diário de campo e posterior sistematização e interpretação dos dados através do método de análise de conteúdo. Pautam-se as reflexões estabelecidas pela perspectiva histórico-crítica. Os resultados sinalizam potencialidades da educação popular, materializada no método pedagógico do IEJC, para o desvelamento da questão social, em suas dimensões de desigualdades e também de resistências.
Keywords: Educação popular; Educação; Veranópolis (RS); Popular education; Education; Veranópolis (Brazil)